Long-term efficacy and safety of dupilumab for moderate-to-severe atopic dermatitis: a prospective real-world cohort study in China - Wang, Yuyi; Jia, Ruiling; Hu, Qin; Tao, Xiao; He, Qi; Luo, Guangying; Xiong, Qiong; Zhang, Zhongyu; Xiao, Yujuan; Liu, Yi (Frontiers in Immunology, 2024)
Backgrounds Dupilumab has demonstrated remarkable efficacy and safety in clinical trials for moderate-to-severe atopic dermatitis (AD). However, long-term real-world evidence, especially in the Chinese population, remains limited.Objective To investigate the long-term efficacy and safety of dupilumab for moderate-to-severe AD in a real-world clinical setting in China and analyze factors that may influence its long-term treatment outcomes.Methods This prospective, observational real-world study included moderate-to-severe AD patients from the AD cohort of the dermatology department of Chongqing Hospital of Traditional Chinese Medicine who received dupilumab treatment for≥52 weeks. Efficacy and adverse events were assessed at baseline, weeks 4, 16, 24, and 52. Multivariate logistic regression analysis was used to identify predictive factors for achieving EASI 50 and EASI 75 at week 52.Results A total of 124 patients were included. At week 52, EASI, SCORAD, IGA, NRS, and DLQI scores were significantly improved compared to baseline. The proportions of patients achieving EASI-50/75 were 50.81%/29.84%, 72.58%/42.74%, 75%/53.23%, and 67.74%/41.94% at weeks 4, 16, 24 and 52, respectively. Female sex, absence of atopic comorbidities, higher baseline EASI, and medication 2 compliance were positive predictive factors for 52-week EASI-50/75. Eosinophil elevation predicted lower EASI-50 attainment. Nineteen adverse events occurred during the 52-week period (incidence rate: 14.52%), mostly mild and manageable.Conclusions Dupilumab demonstrated significant efficacy and a low incidence of adverse events over 52 weeks in Chinese patients with moderate-to-severe AD, making it an effective and safe long-term treatment option. Predictive factors were identified to guide treatment optimization.